Reductions in acute medication use and healthcare resource utilization in patients with chronic migraine: a secondary analysis of a phase 3, randomized, double-blind, placebo-controlled study of galcanezumab with open-label extension (REGAIN). (31st December 2022) - Tobin, Joshua A.; Joshi, Shivang; Ford, Janet H.; Nichols, Russell M.; Foster, Shonda A.; Ruff, Dustin; Detke, Holland C.; Aurora, Sheena K.
Abstract: Aims: To analyze secondary objectives of the REGAIN study related to acute headache medication use and healthcare resource utilization (HCRU) in patients with chronic migraine treated with galcanezumab, a monoclonal antibody to calcitonin gene-related peptide. Methods: Adults with chronic migraine ( N = 1, 113) were randomized (2:1:1) and treated with double-blind monthly injections of placebo, galcanezumab-120 mg, or galcanenzumab-240 mg for 3 months, followed by a 9-month open-label extension with 120 or 240 mg/month galcanezumab. Headache and medication information was collected by daily eDiary. HCRU was reported for the 6 months before randomization, monthly thereafter, and converted to rate per 100-patient-years. Results: At baseline, 63–64% of patients met criteria for acute headache medication overuse. At Month 3, incidence of headache medication overuse in the galcanezumab groups (33% and 33%) was significantly lower than in the placebo group (46%, both p < .001) and was 16% and 23% in the previous-galcanezumab groups at Month 12. From a baseline of 14.5 to 15.5, reduction in mean number of monthly migraine headache days with acute headache medication use was also significantly greater in the galcanezumab groups at Month 3 (−4.2 and −4.9) than in placebo (−2.6, both p < .001), with reductions of −6.8 and −7.6 in the previous-galcanezumab groups at Month 12. Migraine-specific HCRU rates decreased for all groups, with no significant between-group differences at Month 3. At Month 12, in the two previous-galcanezumab groups, emergency room visits decreased by 58% and 75%, hospital admissions by 100%, and healthcare professional visits by 54% and 67%. Limitations: Only 3 months of double-blind, placebo-controlled data, a longer HCRU recall period for baseline than postbaseline, and patients receiving care in the clinical trial itself, may limit generalizability. Conclusions: Treatment with galcanezumab resulted in significant reductions in headache medication overuse and migraine headache days requiring acute medication use, with notable reductions in migraine-specific HCRU.